Evaluation the body conformation of Limousin candidate bulls in farm performance test - Tőzsér, János; Fazekas, Natasa; Szűcs, Márton (Animal welfare, Ethology and Housing Systems (AWETH), 2022)
Authors studied the conformation of Limousin candidate bulls (n=311, farms=30) in 2021. Six body measures – height at withers, cm, rump / tail height, cm, length of back, cm, width of shoulders, cm, width at hip bone, cm, pin width, cm – and two conformation traits (muscularity, score, leg, score) and live weight were analysed.Live weight of bulls taking part in the study (mean: 455 kg, age: 420±30 days) was in concordance with previous French and Hungarian data. Tail height (132 cm) being higher than wither’s height (123 cm) suggest young bulls still maturing, their height is going to grow. Minimum (63 cm) and maximum (94 cm) values of back length mean that animals are well developed according to their age. Current data of hip and pin width of candidate bulls prove a good base for maintaining cow’s calving ease in the breed when going to be used for stud. Mean conformation score for muscularity and feet was around 7. Feet score 6 was accompanied with muscularity scores 6 and 7, with at least 440 kg average live weight. Animals scored 8 for feet got scores 7 or 8 for muscularity, with 460 kg live weight. Mean score 8 was paired with more advantageous, lower SE value.Evaluating live weight by wither’s height categories, taking into consideration muscularity and feet scores suggests that live weight increased by increasing wither’s height in all categories. Positive, moderate correlations of live weight with wither’s height (r=0,613) and tail height (r=0,593) are in concordance with literature data. The correlations of conformation scores with live weight and body measures were different direction and loose.Maturity, body measure data, muscularity and feed structure of animals studied give a chance significantly improving the production of the consecutive if the best ones are going to be used for stud.
Keywords: Limousin candidate bulls; body measures; conformation